Policy on Sustainable Transport in England: The Case of High Speed 2 - Banister, David (European Journal of Transport and Infrastructure Research, 2018)
The achievement of sustainable transport is often a clearly stated objective of government policy, but in England there is no National Sustainable Transport Strategy (NSTS). This paper outlines the nature of sustainable transport arguing for a strategic approach that takes account of the means to reduce travel through substitution and shorter trips, as well as making best use of all modes and reducing reliance on carbon-based energy sources. It reviews the recent austerity phase of UK transport policy (2010-2015) where revenue support has been cut, but capital expenditure has increased, and it comments on the difficulties of making decisions on large scale transport infrastructure projects in the absence of a NSTS. The recent policy statements and initiatives on transport and sustainability are covered, looking backwards and forwards. It then takes the case of High Speed 2 (HS2) and identifies five main narratives in the debates over the arguments in support of this huge investment. It seems that sustainable transport has not been a central part of that debate, and there is a need to reframe the discussion on HS2, as part of a NSTS.